2019
DOI: 10.33508/bw.v7i1.1848
|View full text |Cite
|
Sign up to set email alerts
|

The Interlanguage Pragmatics of Greetings

Abstract: The present study centers on interlanguage and cross-cultural pragmatics. It investigates semantic formulas (SF) in the speech act of greeting as performed by Russian EFL learners. In particular, it compares the non-native speakers' (NNS) and native speakers' (NS) production of SF in terms of number, frequency, and content. A Free Discourse Completion Test (FDCT) containing 16 situational prompts elicited greetings by the English NNSs and NSs. The results demonstrate significant differences in NS and NNS produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…Nevertheless, the transfer has two sided implications, success transfer and failure transfer, based on the chosen speech style and topic. This finding echoed Shleykina's (2019) finding who found that among the major factors that influenced the L2 production of greetings are induced instruction, L1 transfer, low competence in a particular greeting phrase or strategy and desire to sound polite. Thus, the findings suggest the importance of exposure to and the understanding of the cultural context of a target language in choosing appropriate greetings among L2 in an interlanguage context.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Nevertheless, the transfer has two sided implications, success transfer and failure transfer, based on the chosen speech style and topic. This finding echoed Shleykina's (2019) finding who found that among the major factors that influenced the L2 production of greetings are induced instruction, L1 transfer, low competence in a particular greeting phrase or strategy and desire to sound polite. Thus, the findings suggest the importance of exposure to and the understanding of the cultural context of a target language in choosing appropriate greetings among L2 in an interlanguage context.…”
Section: Resultssupporting
confidence: 73%
“…The first one was by Ebsworth et al (1996). The second one is by Shleykina (2019). Ebsworth, et al (1996) and Shleykina (2019) demonstrate precisely on how to classify greetings data.…”
Section: Framework Of Analysismentioning
confidence: 99%
See 3 more Smart Citations